Epistemic Negotiations between Javanese Traditional Healing Knowledge and State Medical Rationality - Zahrotul Zulkia; Dian Safitri; Sadyah Rofifatunnisa; Moh. Ammar Davidin; Amilatul Khasanah (Kamali: Jurnal Ilmu Agama, 2026)
The integration of traditional medicine into the formal health system in Indonesia encourages standardization, objectification, and biomedical-based legitimization that often clash with traditional Javanese healing knowledge rooted in experience, social relations, and local cosmology. Although health policies increasingly open up space for traditional practices, studies of how the epistemic boundaries between local knowledge and state medical rationality are negotiated in institutional practice remain limited. This study aims to analyze the mechanisms, dynamics, and implications of epistemic negotiations between traditional Javanese healing and state medical rationality within formal health services. The study uses a qualitative approach based on library studies and critical discourse analysis of academic literature, health policy documents, traditional medicine regulations, and medical and health policy publications in Indonesia. Epistemic negotiations occur through three mechanisms: first, conceptual hybridization, namely the effort to translate traditional healing practices and concepts into a biomedical terminology framework to gain institutional legitimacy; second, the process of classification and standardization through regulation, certification, and categorization of traditional practices that symbolically limit the epistemic space of local knowledge; Third, the discursive adaptation strategies of traditional actors who repackage healing practices to be compatible with modern health logic without completely abandoning community cosmologies and experiences. These findings suggest that the integration of healing systems is not merely a technical, institutional process but rather an arena of epistemic negotiation fraught with power relations, in which biomedicine functions as the dominant knowledge regime while still opening up space for agency and the reinterpretation of local knowledge.